Research and use of biochar in Costa Rica - Soto-Muñoz, Gabriela (2025)
Introduction. Universities, private companies, non-governmental organizations, and producers’ organizations have conducted research on biochar in Costa Rica in the last 15 years. Objective. To compile observed results in technical documents (bulletins, reports) and scientific documents (scientific papers and theses) related to the use of biochar in Costa Rica. Content. Different furnace designs are presented, with a predominant of the small-scale tin furnace and temperatures between 400 and 600 °C. The raw materials used to produce biochar are wood residues (Gmelina arborea, Cordia alliodora), firewood from coffee and banana agroforestry systems, bamboo, sugarcane stubble, and oil palm stalk. Methodologies have been developed to characterize biochar such as elemental analysis, proximate analysis, and nutrient content. Conclusions. Positive results have been observed in crop development, in acidic soils (doses between 10 and 20 t ha-1) cropped with oil palm and vegetables. No significant increases in crop development were seen with the application of biochar in soils with high cation content (Inceptisols) and volcanic ash derived soils (Andisols) in cocoa, oil palm, and vegetables. Significant improvements in water retention were seen at doses of 30 t ha-1 in sandy soils and a significant decrease in the incidence of Radophulus similis and Fusarium oxysporum in banana was observed, with the addition of biochar + endophytic microorganisms. Biochar production from agricultural byproducts and its use in crops and areas near the production site is recommended to promote the bioeconomy. Future lines of research should include: the improvement of ovens design to work with resistant materials such as oil palm fiber, evaluation of the biochar impact on water, nutrients, and pesticides retention, as well as crop productivity in acid and sandy soils.